2016
DOI: 10.1530/erc-16-0306
|View full text |Cite
|
Sign up to set email alerts
|

WOMEN IN CANCER THEMATIC REVIEW: Diverse functions of DNA methylation: implications for prostate cancer and beyond

Abstract: Prostate cancer is one of the most common malignancies in men worldwide. Current clinical screening ensures that most prostate cancers are diagnosed while still organ confined, but disease outcome is highly variable. Thus, a better understanding of the molecular features contributing to prostate cancer aggressiveness is being sought. For many cancers, aberrant genome-wide patterns of cytosine DNA methylation in CpG dinucleotides distinguish tumor from normal tissue and contribute to disease progression by alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Finally, it is important to note that DNA methylation-regulated APA may not be restricted to the 546 candidates we uncovered using the HCT116/DKO comparison since these cells do not capture tissue-and cell type-specific DNA methylation patterns that exist. This complexity in genome organization, epigenetic variation, and alternative poly(A) site usage highlights an intersection between epigenetic regulation and transcriptome diversity that warrants further studies (Sweet and Ting, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important to note that DNA methylation-regulated APA may not be restricted to the 546 candidates we uncovered using the HCT116/DKO comparison since these cells do not capture tissue-and cell type-specific DNA methylation patterns that exist. This complexity in genome organization, epigenetic variation, and alternative poly(A) site usage highlights an intersection between epigenetic regulation and transcriptome diversity that warrants further studies (Sweet and Ting, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Tumors often exhibit abnormal patterns of cytosine DNA methylation in CpG dinucleotides, which contribute to disease progression. In prostate cancer, a high grade-specific difference in DNA methylation has been observed in gene promoters, gene bodies, and gene 3' ends [ 44 ]. In this study, we found that DNA methyltransferases were highly expressed in the CCNL2 high group.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, this process occurs on cytosine residues present at CpG dinucleotides commonly found in large clusters named CpG islands, which are predominantly located at the 5′ end of genes, occupying approximately 60% of human gene promoter regions [20,23,24]. Although gene promoter hypermethylation is associated with transcription repression of the nearby gene ( Figure 4), depending on DNA methylation genomic location, it can display different functions [22,25]. Epigenetic gene silencing by DNA promoter methylation may occur either directly, by blocking transcription factors to prevent binding to target sites in or near the promoter, or indirectly, through binding of methyl-CpG-binding proteins (MBP), which can recruit other enzymes like DNMTs and histone deacetylases (HDAC), leading to chromatin conformation changes that further repress gene transcription [20,22].…”
Section: Dna Methylationmentioning
confidence: 99%